ECOLOGICAL AND PSYCHOLOGICAL CARRYING CAPACITY OF THE GUNUNG PADANG TOURISM AREA - Syafa'atinnisa Syafa'atinnisa; Noril Milantara; Fakhruzy Fakhruzy (Sylva Jurnal Ilmu-ilmu Kehutanan, 2026)
Mount Padang has high tourism potential due to its beautiful natural panorama, historical value, and accessibility. The increasing number of visits to Mount Padang every year shows the popularity of this area. Ecological carrying capacity emphasizes the ability of the environment to support tourism activities without causing damage. While psychological carrying capacity is related to the comfort of visitors in enjoying a good tourist atmosphere. This study aims to calculate the ecological carrying capacity of Mount Padang based on the parameters of area size, usage capacity, and number of visits. As well as analyzing psychological carrying capacity based on the level of visitor comfort towards crowds. The method used in this study is a quantitative descriptive approach with carrying capacity analysis based on the Carrying Capacity formula. Ecological carrying capacity includes physical carrying capacity (PCC), real carrying capacity (RCC), and effective carrying capacity (ECC). Psychological carrying capacity analysis was conducted by distributing questionnaires to 40 respondents using a Likert Scale. The research results show that the physical carrying capacity of the Gunung Padang area is 500 people/day, the actual carrying capacity is 240 people/day, and the effective carrying capacity is 600 people/day. The majority of visitors feel comfortable, safe, connected to nature, and satisfied with the area's atmosphere, although several aspects such as facilities and visitor density still need to be improved. Therefore, the management of Gunung Padang tourism needs to pay attention to the balance between the capacity of the tourist area and the psychological comfort of visitors to support sustainable tourism development.support